Microwave Assisted Synthesis of Pyrimidines in Ionic Liquid and Their Potency as Non‐Classical Malarial Antifolates. Issue 10 (16th August 2016) - Bhatt, Jaimin D.; Chudasama, Chaitanya J.; Patel, Kanuprasad D.
Abstract : Synthesis of pyrazole‐linked triazolo‐pyrimidine hybrids was achieved by employing Biginelli‐type reaction methodology in an ionic liquid (triethylammonium acetate) under microwave irradiation. This method proved to be highly efficient and the ionic liquid employed was found recyclable for up to five consecutive cycles. The synthesized molecules were further screened for their antimalarial efficacy screening out the active scaffoldsJ15, J18, J21, J24, J27, andJ30 . The active molecules were evaluated in an enzyme inhibition study against the active Plasmodium falciparum dihydrofolate reductase ( Pf ‐DHFR), computationally as well as in vitro, demonstrating their potency as DHFR inhibitors. The active entities were also investigated for their oral bioavailability by predicting ADME properties in silico, indicating good bioavailability. Abstract : Pyrazole‐linked triazolo‐pyrimidine hybrids were synthesized by Biginelli‐type reaction methodology in an ionic liquid and screened for their antimalarial efficacy. An enzyme inhibition study against the active Plasmodium falciparum dihydrofolate reductase ( Pf ‐DHFR) demonstrated their antimalarial effect.